Polycyclic aromatic hydrocarbon destruction in star-forming regions across 42 nearby galaxies - Egorov, Oleg V.; Leroy, Adam K.; Sandstrom, Karin; Kreckel, Kathryn; Baron, Dalya; Belfiore, Francesco; Chown, Ryan; Sutter, Jessica; Boquien, Médéric; Canal i Saguer, Mar; Congiu, Enrico; Dale, Daniel A.; et al. (Astronomy & Astrophysics, 2025)
Polycyclic aromatic hydrocarbons (PAHs) are widespread in the interstellar medium (ISM) of near solar metallicity galaxies, where they play a critical role in ISM heating, cooling, and reprocessing stellar radiation. The PAH fraction, the abundance of PAHs relative to total dust mass, is a key parameter in ISM physics. Using JWST and MUSE observations of 42 galaxies from the PHANGS survey, we analyzed the PAH fraction in over 17 000 H ii regions spanning a gas-phase oxygen abundance of 12 + log(O/H) = 8.0 8.8 (Z ∼ 0.2 1.3 Z), and ∼400 isolated supernova remnants (SNRs). We find a significantly lower PAH fraction toward H ii regions compared to a reference sample of diffuse ISM areas at matched metallicity. At 12 + log(O/H) > 8.2, the PAH fraction toward H ii regions is strongly anti-correlated with the local ionization parameter, suggesting that PAH destruction is correlated with ionized gas and/or hydrogen-ionizing UV radiation. At lower metallicities, the PAH fraction declines steeply in H ii regions and in the diffuse ISM, likely reflecting less efficient PAH formation in metal-poor environments. Carefully isolating dust emission from the vicinity of optically identified supernova remnants, we see evidence of selective PAH destruction from measurements of lower PAH fractions, which is, however, indistinguishable at ∼50 pc scales. Overall, our results point to ionizing radiation as the dominant agent of PAH destruction within H ii regions; metallicity plays a key role in their global abundance in galaxies.
CRIS-Team Scopus Importer:2025-12-05
Keywords: Dust; Extinction; Galaxies: ISM; HII regions; Infrared: ISM; ISM: abundances